Idle Talk, Deadly Talk The Uses of Gossip in Caribbean Literature - Rodriguez-Navas, Ana (University of Virginia Press, 2018)
The first book-length study of gossip's place in the literature of the multilingual Caribbean reveals gossip to be a utilitarian and deeply political practice-a means of staging the narrative tensions, and waging the narrative battles, that mark Caribbean politics and culture. Revising the overly gendered existing critical frame, Rodríguez Navas argues that gossip is a fundamentally adversarial practice that at once surveils identities and empowers writers to skirt sanitized, monolithic historical accounts by weaving alternative versions of their nations' histories from this self-governing discursive material. Reading recent fiction from the Hispanic, Anglophone, and Francophone Caribbean and their diasporas, alongside poetry, song lyrics, journalism, memoirs, and political essays, Idle Talk, Deadly Talk maps gossip's place in the Caribbean and reveals its rich possibilities as both literary theme and narrative device.